Engaging students in extended learning conversations to improve their mathematical understanding - McClellan, Lynette (Curtin University, 2012)
The study was undertaken to investigate classroom strategies focused on language that would facilitate cognitive processing and improve mathematical understanding along with examining the link between the strategies and elaborated, extended learning conversations. This involved developing strategies in the mathematics classroom for students to engage in extended learning conversations (elaborated discourse) to develop and demonstrate their understanding of mathematical concepts. The theoretical base for developing the strategies was grounded in the theories of Halliday, Bernstein and Vygotsky and influenced by those working in language development. The foundation for the study was an examination of teacher language usage in the classroom based on the belief that with language being effectively used one could actually make a difference to students’ understanding of mathematics.The study was conducted using a Participatory Action Research design with teacher as researcher working to improve the learning/teaching classroom practice and was carried out with two groups of students in a rural district high school. The first group consisted of year 8, 9 and 10 students and the second group consisted of year 6 and 7 students both in multi– aged classes. Data analysis was undertaken using a Grounded Theory approach. The study commenced early in Term 1 of 2010, with a follow up in the latter stages of Term 2 and was completed with collection of student responses late in Term 4.The learning/teaching strategies that were identified and developed were the Shared Experience, Purposeful Discussion, Blended Instruction and Student Peer Teaching strategies. The identification of these strategies presented a strong case for a Mathematical Linguistic Pedagogy combining elements of mathematical content knowledge and linguistic pedagogy. The strategies presented an approach to teaching and learning that combined elements of constructivist philosophy alongside elements of traditional teaching practice that focus on elaborated use of language. The use of the strategies enabled diagnosis of misconceptions as well as enhancing learning, providing for deep understanding and empowering students to share reflections of their own thought development and processes.